Analysis of the Casing Collapse in Terms of Geomechanical Parameters and Solid Mechanics - Farid Ghodusi; Hossein Jalalifar; Saeed Jafari (Journal of Chemical and Petroleum Engineering, 2019)
Casing collapse is one of the major problems in oil fields, imposing a lot of costs on oil companies. This problem occurs not only at drilling times in some formations but also after the completion and production can lead to many problems. Analysis of the behavior of casing collapse in terms of geo-mechanics and solid mechanics could significantly meet the needs of the oil industry of Iran. In this study, at first, casing collapse behavior is investigated by considering the formation creep and casing production defects using numerical methods. Then, the effect of some solid mechanics parameters on the casing collapse is investigated. The results showed that casing construction defects, such as ovality and eccentricity and residual stress, could greatly reduce the casing collapse resistance. The resistance reduction of the casing is about 30.37, 9.65, and 46.87 percent respectively, so that when the casing is placed into the well, it undergoes high strain and finally could be reached to collapse. In addition, it was found that the construction defects show a higher effect on casing collapse than the salt rock creep.